2017
DOI: 10.1016/j.jclepro.2016.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of eco-labels on fresh produce in Flanders (Belgium) highlights a potential intention–performance gap for the supply chain

Abstract: When it comes to making sustainable food purchasing choices, consumers trust on information provided to them by eco-labels. This article studies the labels for fresh produce available to consumers in Flanders (Belgium), concluding that the existing labelling landscape fails at enabling consumers to make adequate decisions for purchasing environmentally sound food. A consumer survey supports the need for additional information on the sustainability of fruits and vegetables.A potential intention-performance gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In a previous study we concluded that the current labels on fresh produce in Flanders (Belgium) fail at providing consumers with adequate information on the environmental friendliness of fruits and vegetables (Goossens et al 2017b). In that paper, we suggested using the life cycle assessment approach (LCA), covering the entire food chain and taking into account multiple impacts, in order to move towards performance based information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we concluded that the current labels on fresh produce in Flanders (Belgium) fail at providing consumers with adequate information on the environmental friendliness of fruits and vegetables (Goossens et al 2017b). In that paper, we suggested using the life cycle assessment approach (LCA), covering the entire food chain and taking into account multiple impacts, in order to move towards performance based information.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper (Goossens et al 2017b), we further recommend taking into account situational parameters such as time of consumption, origin, production and distribution mode to assess environmental impacts associated with the particular case of fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…Despite doubts around attitudes toward sustainability labelling [19,67] this review found a preference for environmental and social responsibility product attributes. In 57% of studies it was found that consumers evaluated environmental and social responsibility labelling information more favourably than nutrition labelling information.…”
Section: Summary Of Key Findingsmentioning
confidence: 90%
“…Previous studies on environmental labels and declarations focused mainly on topics such as consumer interpretation of recycling signs on packaging [21] and the influence of eco-labels on making sustainable purchasing choices [22]. Research studies on participatory design of environmentally friendly messages, however, have never been seen.…”
Section: Introductionmentioning
confidence: 99%